Analisis Tingkat Kecemasan Pada Tenaga Keperawatan Di Ruang Isolasi Khusus Perawatan Pasien Covid 19: Literature Study - Fransisco Irwandy (NHM PRESS, 2023)
Research is a literature study. In the strategy of looking for journals, the framework used is PICOT. The keywords used are “Anxiety AND Nurses AND Covid 19”. The data sources used are the e-resources database of the National Library, Pubmed and Google Scholar in the form of articles or journals. The inclusion criteria in this study were national and international journals from different databases and related to research variables namely Anxiety and Covid-19 Patient Nurses and the deadline for article publication within the last 5 years (2016-2021). The exclusion criteria for this study were national and international journals from different databases and had nothing to do with research variables, no intervention was given, not Anxiety and Patient Nurses not Covid-19 and the time of publication of articles was more than 5 years. In the search for articles using 3 databases, each found from the National Library of 119 search results, PubMed 358 search results and Google Scholar 836 search results. After being disqualified regarding the year of publication, namely the last 5 years and selecting duplicate articles, 327 articles were obtained, and finally 6 articles that met the criteria. Of the 6 articles that have been reviewed and found, most health workers experience anxiety. Based on a literature review of 6 research journals, it can be concluded that health workers experience anxiety while caring for clients with Covid-19 because of the additional working hours and workload and the lack of personal protective equipment.